Algebraische Zahlentheorie: 12.08. bis 18.08.1990 - Jehne, Wolfram; Leopoldt, Heinrich-Wolfgang; Roquette, Peter (Tagungsbericht, 1990)
Graham R. Everest; Albrecht Fröhlich; Erich Lamprecht; Jürgen Neukirch; Jannis A. Antoniadis; Werner Bauer; Eva Bayer-Fluckiger; Sigrid Böge; Jan Brinkhuis; Christopher Deninger; G. Frei-Imfeld; Gerhard Frey; Wulf-Dieter Geyer; Barry William Green; Franz Halter-Koch; Dan Haran; Uwe Jannsen; Moshe Jarden; Wolfram Jehne; Christian Ulrik Jensen; Ernst Kani; Ivan Kausz; Ernst Kleinert; Helmut Koch; Radan Kucera; Klaus Künnemann; Johann B. Leicht; Hendrik W. Lenstra; Heinrich-Wolfg. Leopoldt; Armin Leutbecher; Falko Lorenz; Manohar L. Madan; Gunter Malle; B. Heinrich Matzat; Leon R. McCulloh; Tauno Metsänkylä; Katsuya Miyake; Enric Nart; Olaf Neumann; Robert W. K. Odoni; Hans Opolka; Albrecht Pfister; Florian Pop; Alexander Prestel; Hans-Peter Rehm; Jürgen Ritter; Peter Roquette; Reinhard Schertz; Claus-Günther Schmidt; Rene Schoof; Michael Spieß; Peter Stevenhagen; Jörg Wildeshaus; Kay Wingberg; Zdzislaw Wojtkowiak; Ernst-Wilhelm Zink